Beliefs regarding SARS-COV-2 vaccine in patients with transfusion-dependent thalassemia - Kakkar, Shruti; Sharma, Pranjl; Sidhu, Sukhmani; Kamboj, Shaina; Luthra, Suraj; Kapoor, Rashmi; Dewan, Priyanka (International Journal of Research in Medical Sciences, 2022)
Background: SARS-CoV-2 vaccination drive generated varying responses in the general public. This study aimed to assess the vaccination acceptance amongst patients with thalassemia and to elucidate their beliefs regarding SARS-CoV-2 vaccines. Methods: A prospective observational study was done involving thalassemia patients above the age of 18 years in the thalassemia day care center of our hospital. Results: The study assessed 145 patients with a male to female ratio of 1.5:1 and a mean age of 25.6±6 years. Seventy-six (52.4%) of the study population had already been vaccinated with the first dose, 25.5% (n=37) were willing to get vaccinated, however, 22% were vaccine-hesitant. Vaccine hesitancy was 25.5% in males compared to 16.9% in females. The fear of adverse effects to the vaccine is a major deterrent to the vaccination. Patients considered themselves at high risk of COVID-19 disease and adverse effects of the SARS-CoV-2 vaccine. Conclusions: Vaccine hesitancy was observed in 22% of patients. A significantly higher proportion of these patients considered vaccines unsafe and ineffective. Public sharing of safety and efficacy data may help in improving trust in the vaccine.